Ensino de ciências na era da pós-verdade : as fake news como estratégia de ensino - Britto, Daniella Maria Coelho de (2022)
The terms post-truth and Fake News have been gaining ground in public discussions over the past few years. Although the terms cited have become more popular recently, they designate actions that have always existed in the history of humankind. The discrediting of science in relation to issues that until then were considered consolidated suggests that we are living in the post-truth era, which is favourable for the dissemination of Fake News. This context exposes the need to address this issue in Science classes in order to improve students critical thinking. The aim of this research is to investigate how the participants of the Institutional Scholarship Program for Teaching Initiation (PIBID) evaluate a didactic sequence that uses Fake News as a science teaching strategy in the post-truth era. The main problem of this investigation is: How do the PIBID participants of the Chemistry subproject, from UFMT evaluate a didactic sequence that uses Fake News as a teaching strategy? Based on this questioning, this work sought to analyze the discourse present in different Fake News with potential to be worked on Science classes, related to the current Covid-19 pandemic. In addition, in order to understand the issue raised, a didactic sequence was developed to propose the use of Fake News in Science teaching, as a teaching strategy. The didactic sequence (DS) was evaluated by the participants of the Institutional Program for Teaching Initiation Scholarships (PIBID) of the Chemistry course at UFMT, in the city of Cuiabá-MT. Our results showed the low familiarity of the subjects with the term post-truth. With regard to the subjects' relationship with Fake News, we found that all subjects have already received some false news, and according to most of them the platforms where they are most exposed to this type of news are WhatsApp® and Facebook®. When asked about how often they check the origin of the news before sharing it, two of the three professors stated that they never or almost never check the origin of the information shared. With regard to the analysis of DS, the subjects understood that it presents itself as an effective didactic-pedagogical activity to work critically with the Fake News theme. In relation to the main difficulties or problems linked to the development of DS mentioned by the subjects, the low participation of students during classes, especially during remote classes, the absence of internet and the difficulty of carrying out group work during classes stands out. remote classes. Despite the DS having been developed to be applied to Basic Education students, after an interview with one of the teachers, we realized the potential that DS has to be worked on in the initial and continuing education of teachers. Although DS can be adapted to different contexts, such as face-to-face or remote teaching, and to different disciplines and contents, we consider that the fact that DS requires the use of the internet at different times is a limiting factor.